2022
DOI: 10.1016/j.neuron.2022.01.005
|View full text |Cite|
|
Sign up to set email alerts
|

Orthogonal representations for robust context-dependent task performance in brains and neural networks

Abstract: Orthogonal representations for robust contextdependent task performance in brains and neural networks Highlights d We trained artificial neural networks and humans on contextdependent decision tasks d Initial weight variance determined the network's representational geometry d Human fronto-parietal representations were similar to those of low-variance networks d Theory of nonlinear gating explains how these are formed in neural networks and brains

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
127
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(173 citation statements)
references
References 54 publications
19
127
3
Order By: Relevance
“…5a-c,e). Previous studies have shown that the brain uses private, orthogonal subspaces to disentangle information about different aspects of a task (Mante et al 2013; Kaufman et al 2014; Sheahan, Franklin, and Wolpert 2016; Bagur et al 2018; Flesch et al 2022). For example, population recordings in the premotor cortex during a context-dependent perceptual task show that monkeys use the context cue to “displace” the state of the network such that the encoding of the irrelevant stimulus feature is decoupled from the choice axis (Mante et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…5a-c,e). Previous studies have shown that the brain uses private, orthogonal subspaces to disentangle information about different aspects of a task (Mante et al 2013; Kaufman et al 2014; Sheahan, Franklin, and Wolpert 2016; Bagur et al 2018; Flesch et al 2022). For example, population recordings in the premotor cortex during a context-dependent perceptual task show that monkeys use the context cue to “displace” the state of the network such that the encoding of the irrelevant stimulus feature is decoupled from the choice axis (Mante et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in which human participants learned to perform two tasks while in a functional magnetic resonance (fMRI) scanner provides some evidence for our predictions[9]. The representations of a high-dimensional stimulus with two task-relevant dimensions (one which was relevant in each of two contexts) were studied in both the fMRI imaging data and in neural networks that were trained to perform the two tasks (the setup in this work is similar to certain manipulations in our study, particularly to the partial information case shown in fig.…”
Section: Discussionmentioning
confidence: 76%
“…Further, experimental work in the hippocampus and prefrontal cortex has shown that representations of the sensory and cognitive features related to a complex cognitive task, also support generalization[5]. We refer to representations of task-relevant sensory and cognitive variables that support generalization – like in these examples and others[9, 10] – as abstract representations.…”
Section: Introductionmentioning
confidence: 99%
“…As such, these learning dynamics naturally give rise to low-dimensional neural representations. Such learning dynamics may thus underlie the popular idea in neuroscience of low-dimensional neural manifolds (see Flesch et al (2022)).…”
Section: Discussionmentioning
confidence: 99%